How the word is passed [compact disc, unabridged] : a reckoning with the history of slavery across America - Smith, Clint (Hachette Audio, 2021)
A civics lesson, a work of cultural reclamation, and a beautiful and brilliant meditation on the persistence of the past. Discover poet, educator, and co-host of Pod Save the People Clint Smith's bold first-person retelling of Black American history.